KNOWLEDGE, PREPAREDNESS, AND BARRIERS TOWARD RECEIVING INFLUENZA VACCINE AMONG STUDENTS AT UNIVERSITY OF KUFA - Kadhim, Jihad Jawad (PT. Antis International Publisher, 2025)
Objective: To assess knowledge, perceived barriers, and willingness toward influenza vaccination among undergraduate students at the University of Kufa, Iraq, to inform targeted health promotion strategies. Method: A cross-sectional descriptive study was conducted from February to March 2025 with 94 convenience-sampled undergraduate students from five colleges at the University of Kufa. Data were collected using a validated 32-item questionnaire assessing demographics, influenza vaccine knowledge, barriers, and willingness. Statistical analyses included descriptive statistics and correlation tests using SPSS. Results: Participants demonstrated moderate knowledge levels: 60.64% had fair knowledge and 39.36% good knowledge regarding influenza vaccination. Most (64.89%) perceived moderate barriers, including misperceptions about vaccine safety, fear of side effects, and accessibility challenges. Willingness to vaccinate was moderate in 58.51% but poor in 38.30% of students. Correlation analysis showed no significant relationships between knowledge, barriers, and willingness, indicating complex factors influencing vaccine acceptance beyond knowledge alone. Novelty: The findings reveal moderate awareness and willingness toward influenza vaccination, tempered by perceived barriers among university students. Vaccine acceptance appears driven by a multifaceted interplay of cognitive, emotional, and structural factors. Tailored, multifactorial interventions combining education, barrier reduction, and improved accessibility are essential to increase vaccine uptake in this population.